2009
DOI: 10.1128/aem.00905-09
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency of Copper Ion Homeostasis Causes Freeze-Thaw Injury of Yeast Cells as Revealed by Indirect Gene Expression Analysis

Abstract: Saccharomyces cerevisiae is exposed to freeze-thaw stress in commercial processes, including frozen dough baking. Cell viability and fermentation activity after a freeze-thaw cycle were dramatically decreased due to freeze-thaw injury. Because this type of injury involves complex phenomena, the injury mechanisms are not fully understood. We examined freeze-thaw injury by indirect gene expression analysis during postthaw incubation after freeze-thaw treatment using DNA microarray profiling. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Interestingly, it is known that the transcription of these genes is under the control of the transcription factor Mac1 [28] , [34] . Takahashi et al previously reported that copper ion homeostasis regulated by Mac1 is important for tolerance to freeze-thaw stress, which is one of the oxidative stresses [32] . Based on these findings, we speculated that there is some relevance between Mac1 and NO-mediated oxidative stress tolerance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it is known that the transcription of these genes is under the control of the transcription factor Mac1 [28] , [34] . Takahashi et al previously reported that copper ion homeostasis regulated by Mac1 is important for tolerance to freeze-thaw stress, which is one of the oxidative stresses [32] . Based on these findings, we speculated that there is some relevance between Mac1 and NO-mediated oxidative stress tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Ace1 is activated by the binding of copper ions to its cysteine residues [31] . Copper homeostasis is important for tolerance to oxidative stress as well as freeze-thaw stress [32] , whereas copper ion is a cofactor for the Cu,Zn-superoxide dismutase Sod1, which is one of the crucial antioxidative enzymes [7] .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that SOD1 and the ER stress marker ERP29 gene expression were significantly up-regulated in response to freeze-thaw stress in primate ovarian tissue [81]. In yeast, genes expression for protein chaperones such as SSA4, HSP26, HSP42 were found to be up-regulated in response to freeze-thaw stress when cells were frozen in the absence of cryoprotectants [87]. In mammals, all three arms of the UPR may be activated during cryopreservation.…”
Section: Cryopreservation and Ros Productionmentioning
confidence: 99%
“…At the end of the fermentation, the proportion of cells able to form colonies (CFU) after 2 days on YPD agar plates was determined and referred to as the growth recovery (%). This parameter is usually assimilated as an indirect measure of cell viability in microbiology (62). Finally, the cell size was measured at the end of alcoholic fermentation using a particle counter (Z2 Coulter counter; Beckman Coulter, Villepinte, France) and the mean cell size (diameter [m]) was calculated and used for further analyses.…”
mentioning
confidence: 99%